Optimum Building Design Variables in a Warm Saharan Mediterranean Climate Zone - Aiman Albatayneh; Tarek Tayara; Mustafa Jaradat; Murad Al-Omary; Muna Hindiyeh; Dariusz Alterman; Manal Ishbeytah (International Journal of Photoenergy)
This research contributes to making residential buildings more efficient in the city of Azraq, Jordan, which is located in a warm climate zone in the Saharan Mediterranean region (classified as a hot desert climate according to the Köppen climate classification). It involved the optimisation of several envelope parameters with the aim of reducing the usage of energy within a normal structure occupying an area of 186 m2 without the occupants’ involvement in saving energy in the building to solely measure the building envelope’s thermal performance. The DesignBuilder software was used for the sensitivity analysis using 12 design variables, which enabled their significance for both cooling and heating loads. The selected variables were separated into two categories based on their level of significance: a group with higher importance (window to wall %, local type of shading, ground floor building, natural rate of ventilation, rate of infiltration, kind of glazing, and flat roof structure) as well as a group with lower importance (partition construction, site position, construction of outside walls, kind of window blinds, and window shade control timetable); these variables will save a significant amount of heating and cooling energy.